Estudo de inserção de jogos computadorizados como recurso complementar ao ensino de leitura - Marques, Leonardo Brandão (Universidade Federal de São Carlos, 2014)
The literature cites educational games as a procedure that increase the spontaneous engagement in educational task and assist the retention of what was learned. Choice procedures and the identification of preference among different teaching procedures can be taken as an indicator of further spontaneous engagement .Were proposed two complementary studies to investigate the influence of electronic games in the learning of reading: The Study 1 tested an application of a software and a procedure for teaching reading in large-scale (a school environment) with 11 participants; the Study 2 incorporated this same teaching procedure in a game (gamified version) and assessed the preference between the game and the standard condition of teaching (without game) among 27 elementary students. The results indicated that for both conditions (standard and gamified) the teaching program was effective in teaching basic reading skills. Most participants presented preference for the gamebased teaching condition format. The gains in reading performances were kept in this condition and the number of repetitions of the teaching procedure was also lower in game situation. It has not been possible to identify a preference between game or the conventional procedure for about 30% of the participants. Participants who showed preference for Game condition tended to repeat less blocks of training components of each teaching session. A task who asked the students to choose between the default condition and return to the classroom indicated that participants with preference for Game condition remained engaged in teaching procedure when was given the opportunity to return to the classroom. The discussion focuses on the parameters used in the choice task, pointing manipulations that optimizes the method to measure the preference, in order to make it more sensitive to different measures of the game as a motivational factor.
Study of computerized games insertion as additional resource to teaching reading
Keywords: Leitura; Leitura - ensino; Jogos educativos; Escolha (Psicologia); Gamificação; CIENCIAS HUMANAS::PSICOLOGIA